(untitled) (Jurnal Intek Akuakultur, 2019)
Research on the effect of addition of phytase enzymes in artificial feed on Barramundi (Lates calcarifer, Bloch) feed efficiency and growth, this research was held at BPBL Batam. The purpose of this study was to determined dosage of phytase enzymes to be added to medium protein feed (PF) to efficiently feed and increase the growth of Barramundi. The methode used in this study was RAL, using 4 treatment and 3 replications. The treatments used in this study were: A) 0 g phytase enzymes, B) 0,5 g phytase enzymes, C) 1 g phyase enzymes, D) 1,5 g phytase enzymes per kg of PF artificial feed. The results of feed efficiency and daily weight growth of this study showed that treatment D was the best results 20,41 % and 5,1 % respectivly.